2020
DOI: 10.1155/2020/8882930
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of Silver Nanoparticles in the Prevention and Arrest of Dental Caries

Abstract: Dental caries is one of the major diseases of the oral cavity affecting humans worldwide. Different alternatives have been used for its control, but its incidence and prevalence are still high. On the other hand, silver has been used for centuries due to its antimicrobial properties. With advances in nanotechnology, the use and research in nanomaterials has increased, recently, and silver nanoparticles have become an essential part of the dental practice, giving materials physical and chemical improvements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Subsequent evaluations were done using the DIAGNOdent at three months to evaluate changes in remineralization. The rate of remineralisation was found to be higher than plain water on treatment with silver nanoparticles [16].…”
Section: Silver Nanofluoride (Nsf)mentioning
confidence: 89%
“…Subsequent evaluations were done using the DIAGNOdent at three months to evaluate changes in remineralization. The rate of remineralisation was found to be higher than plain water on treatment with silver nanoparticles [16].…”
Section: Silver Nanofluoride (Nsf)mentioning
confidence: 89%
“…The use of silver nanoparticles in dentistry has gained much attention for its anti-bacterial mechanism and its potential to counteract the drawbacks of silver diamine fluorides (SDF) such as tooth discoloration and gingival inflammation. (1,2,4,25) The effect of topical fluorides on enamel includes enhancing enamel remineralization and preventing demineralization. Previous studies have shown that the presence of fluorides in a solution surrounding the enamel crystals yields them more resistant to acidic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The management of dental caries includes conservative and preventive methods that require early diagnosis to preserve the tooth structure by either arresting caries at an early stage or preventing the initial demineralization process. (2)(3)(4)(5) To date, topical fluorides are considered the most effective method for the prevention of caries occurrence and the arrest of early carious lesions. (4,6,7) Sodium fluoride varnishes are widely used due to the ease and rapid application as well as fast setting on the tooth surface minimizing the common drawbacks of topical fluoride application including swallowing or gagging that may lead to toxicity or dental fluorosis when especially in young children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have suggested their usage in a variety of formulations, with promising results in the treatment of S. mutans , with antibacterial activity 25 times stronger than chlorhexidine, as well as antiviral and antifungal activities [ 93 ]. Composite resin is now the most extensively utilized dental material to treat caries lesions, owing to its cosmetic and load-bearing qualities.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%